2002
DOI: 10.1097/00003246-200207000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide improves pulmonary gas exchange by reducing extravascular lung water in canine model with oleic acid-induced pulmonary edema

Abstract: These findings suggest that atrial natriuretic peptide improves pulmonary gas exchange by reducing extravascular lung water and pulmonary arterial pressure, possibly independently from natriuresis/diuresis in oleic acid-induced pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Because plasma half-lives (t 1/2 ) of ANP were 2.29 Ϯ 1.02 mins (␣-phase) and 15.2 Ϯ 4.75 mins (␤-phase) by the two-compartment model, respectively, the duration and the dose of ANP infusion (1 g/kg/min for 5 hrs) as used in this study seem to be sufficient to maintain its effective plasma concentrations. Although the lower dose (0.2 g/kg/min) of ANP in the rat ameliorated ischemic acute renal failure (10), the higher dose (1 g/kg/min) of ANP used in the present study was shown to cause the potent diuretic effect without affecting MAP in a dog model, as previously demonstrated in our laboratory (13). On the contrary, the gradual decrease in MAP after aortic clamp removal was not observed in the ANP group.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Because plasma half-lives (t 1/2 ) of ANP were 2.29 Ϯ 1.02 mins (␣-phase) and 15.2 Ϯ 4.75 mins (␤-phase) by the two-compartment model, respectively, the duration and the dose of ANP infusion (1 g/kg/min for 5 hrs) as used in this study seem to be sufficient to maintain its effective plasma concentrations. Although the lower dose (0.2 g/kg/min) of ANP in the rat ameliorated ischemic acute renal failure (10), the higher dose (1 g/kg/min) of ANP used in the present study was shown to cause the potent diuretic effect without affecting MAP in a dog model, as previously demonstrated in our laboratory (13). On the contrary, the gradual decrease in MAP after aortic clamp removal was not observed in the ANP group.…”
Section: Discussionsupporting
confidence: 60%
“…In humans, ANP infusion increased creatinine clearance and decreased the need for dialysis in patients with established acute renal failure (12). The use of a lower dose (0.2 g/kg/min) of ANP caused depressor effect in rats (10), whereas an even higher dose (1 g/kg/min) of ANP caused profound natriuretic-diuretic effects without depressor effect in dogs (13). Therefore, it is reasonable to consider that ANP may protect kidney from ischemic damage resulting from suprarenal abdominal aortic cross-clamping during aneurysm repair.…”
mentioning
confidence: 99%
“…Recent evidence suggests that ANP reduces extravascular lung water in the dog model of oleic acid-induced pulmonary edema (Mitaka et al, 2002). This peptide also attenuated brain edema in the rat models of cerebral ischemia (Nakao et al, 1990;Naruse et al, 1991), intracerebral hemorrhage (Rosenberg and Estrada, 1995;Rosenberg et al, 1992), or induced hyponatremia (Vajda et al, 2001).…”
Section: Anp Effect On Brain Edema Formationmentioning
confidence: 98%
“…14,15,20 In the lung, protective effects of ANP have been reported against chemical-, oxidant-and high-altitude-induced lung injuries. [23][24][25][26][27] So far, no investigation has shown a protective effect of ANP on I/R injury in lung.…”
mentioning
confidence: 99%